Effect of High CO2 Treatment and MA Packaging on Sensory Quality and Physiological-Biochemical Characteristics of Green Asparagus (Asparagus officinalis L.) during Postharvest Storage - Li-Xia Wang; In-Lee Choi; Ho-Min Kang (Horticulturae, 2020)
Green asparagus is vulnerable to thrips that carry microorganisms and cause deterioration in quality. The effects of 60% CO2 treatment, which is used to kill thrips, combined with perforated (P) or modified atmosphere (MA) packages during cold storage, on the sensory quality and physiological–biochemical characteristics of asparagus were investigated. MA packaging yielded an asparagus shelf-life five days longer than P packaging. The 60% CO2 treatment for 48 h at 4 °C packaged with MA film (CO2-48 h-4 °C-MA) showed a lower number of aerobic bacteria, yeast, and mold. Yellowing of asparagus was retarded, as shown by higher hue angle and chlorophyll content and lower chlorophyllase activity. Also, CO2-48 h-4 °C-MA treatment inhibited the reduction of soluble solids content in asparagus. Likewise, all high CO2 treatments showed lower electrolyte leakage (EL), with CO2-48 h-4 °C-MA demonstrating the minimum EL. The effectiveness of high CO2 on maintaining sensory qualities was observed, with a score higher than 3.0. In conclusion, CO2-48 h-4 °C-MA treatment during cold storage was effective for maintaining post-harvest sensory qualities and physiological–biological traits of asparagus, and provided strong inhibition of microflora growth during the storage period.